Phytochemical composition and antioxidant activity in three basil varieties due to the effect of different solvents - Salas-Pérez, Lilia; Moncayo-Lujan, María del Rosario; Borroel-García, Victoria Jared; Guzmán-Silos, Tania Lizzeth; Ramírez-Aragón, Mercedes Georgina (Revista Mexicana de Ciencias Agrícolas, 2022)
Basil (Ocimum basilicum) is a very important crop in the world and in Mexico for the well-known specialties of Mediterranean cuisine. There is a growing demand for basil in the United States of North America and Europe due to its antioxidant content. Nowadays, to change synthetic antioxidants for natural ones is a trend in the food industry. Interest in analyzing natural, non-toxic and healthy products that work as antioxidants has increased. Basil contains high levels of secondary metabolites. With the aim of determining the extraction potential of different solvents (hexane, methanol, petroleum ether and ethanol) in three varieties of basil (Lemon, Cinnamon and Red Rubin). In the present study, quantification analyses were carried out for total phenolic compounds, with values between 0.5 and 17.9 mg based on gallic acid per gram of sample in dry weight, total flavonoids obtaining values that ranged between 2.4 and 10.8 mg of quercetin per gram of sample in dry weight and determination of antioxidant activity with results between 57.4-409.4 μmol Trolox per gram of sample in dry weight of the three varieties of basil (Lemon, Cinnamon and Red Rubin) and the different solvents as extraction media (methanol, hexane, petroleum ether and ethanol). Results of greater efficiency were obtained for the different variables measured when the solvent used was methanol in the Lemon and Cinnamon varieties and ethanol in the Red Rubin variety, without finding a significant difference to the extraction with methanol.
Keywords: extraction; flavonoids; phenolic compounds; secondary metabolites